Celtic Tradition: The Guiding Force of William Butler Yeats - Karim, Sajjadul (IIUC Studies, 2012)
The folklore, myth, and legends of ancient Celtic traditions inspired William Butler Yeats a lot. By not falling into the trap of overly romanticizing his work, as many other authors of the time would do, Yeats was able to begin a tradition of another sort, the Irish literary tradition. By giving importance on the Irish culture in his work, Yeats fulfilled his own sense of national pride to the delight of his readers and audiences and to the chagrin of many of his English contemporaries who felt that nothing of value or worthy of study could come out of Ireland. From 1890 he was a member of the occult group of the Golden Dawn1, which fuelled his fascination with the mystic symbols of rosicrucianism and cabbalism. Because of these activities his thinking gave an emphasis on magic and apocalypticism that would remain a constant feature of his work. This article aims at exploring the Irish myth, folklore, occultism and the tradition that inspired William Butler Yeats. DOI: http://dx.doi.org/10.3329/iiucs.v6i0.12248 IIUC Studies Vol.6 2010: 53-64